P634 Ustekinumab and vedolizumab as first-line biological therapy for inflammatory bowel disease. A multicenter study based on the ENEIDA registry. (30th January 2023) - Calafat Sard, M; Pascual, I; Nos, P; Barrio, J; Gutiérrez, A; Martín-Arranz, M D; Ricart, E; Gomollón, F; Sierra Ausín, M; Huguet, J M; Guardiola, J; Vera, I; et al.
Abstract: Background: The use of ustekinumab (UST) and vedolizumab (VDZ) as first line therapy for inflammatory bowel disease (IBD) is increasing due to safety reasons and contraindications of anti-TNFs. However, there are no studies evaluating their efficacy and safety in clinical practice under these circumstances. Thus, our aims were to describe bionaïve patients' characteristics starting VDZ or UST and to evaluate treatment persistence of these drugs and their safety profile in this scenario. Methods: Descriptive, retrospective and multicenter study based on the ENEIDA registry (a large, prospectively maintained database of the Spanish Working Group in IBD –GETECCU). All IBD patients never exposed to biological agents who started VDZ or UST as first-line biological treatment were identified. Results: Out of 29, 450 IBD patients ever exposed to biological drugs included in the ENEIDA registry, 924 patients met the inclusion criteria. Of these, 366 (40%) started UST and 558 (60%) VDZ as first line biological therapy. UST group: 48% women, 90% Crohn's disease (43% ileal; 13% colic; 43.5% ileocolic; 31% upper gastrointestinal involvement; 25% stricturing behaviour; 12% penetrating, 18% perianal disease), 10% ulcerative colitis (74% extensive, 17% left-sided, 9% proctitis), 27% had extraintestinal manifestations (EIM). Median age at the beginning of UST was 57 years (IQR 57-70), 17% patients had a past history of malignancy and, 34% had associated comorbidities. UST indication was luminal activity except in 2% for perianal disease and 5% for EIM. At the end of follow-up (median 14 months [IQR 6-30]), 12 patients (3.3%) developed adverse effects (AEs) that led to treatment discontinuation in the majority of them (92%). VDZ group: 44% women, 42% Crohn's disease (44% ileal; 18% colic; 38% ileocolic; 25% upper gastrointestinal involvement; 28% stricturing behaviour; 13% penetrating; 7% perianal disease), 58% ulcerative colitis (50% extensive, 42% left-sided, 8% proctitis), 17% had EIM. The median age at the beginning was 61 years (IQR 48-71), 24% had past history of malignancy and, 34% associated comorbidities. The indication was exclusively luminal activity. At the end of follow-up (median 21 months [IQR 8-36]), 36 patients (6.5%) had AEs, that lead to treatment withdrawal in 67% of them (24 patients). Cumulative treatment persistence rates were 78%, 60% and 50% for VDZ and 85%, 75% and 66% for UST at 12, 24 and 36 months, respectively (P<0.001). Conclusion: In clinical practice, VDZ and UST are used first-line particularly in elderly patients with comorbidities. Both treatments have a good safety profile and a high persistence of treatment, being superior for ustekinumab.